Sosialisasi dan Pelatihan Penyusunan Laporan Keuangan kepada UMKM di Kabupaten Banyumas - Giovanny Bangun Kristianto; Esti Saraswati; Farida Istiningrum (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program aims to provide training in preparing simple financial reports to MSMEs in Banyumas Regency. This activity, which was attended by 20 MSMEs in the culinary sector, focused on increasing understanding of SAK-EMKM, direct practice in preparing financial reports, and assistance related to financial management. The obstacles faced by MSME partners are partly related to minimal capital and marketing. From the capital sector, basically with the existence of financial reports, it is able to bridge financial problems. In addition, information regarding access to capital and HR development strategies was also conveyed. The results of the activity showed an increase in understanding and skills of MSME actors in preparing financial reports, which are expected to support business growth and their competitiveness in the market. Assistance in preparing financial reports for MSMEs is a method to align the problems that arise to make MSMEs in Indonesia more advanced and synergize in building Indonesia.